2016
DOI: 10.5414/cnp86s121
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired acute kidney injury in adults in Africa

Abstract: Aims: We review recent published data on demographics, causes, diagnoses, treatment, and outcome of acute kidney injury (AKI) in Africa. Methods: A review of the incidence, etiology, diagnoses, and treatment of AKI in adults in Africa from studies published between the years 2000 and 2015. Results: The incidence of AKI in hospitalized patients in Africa ranges from 0.3 to 1.9% in adults. Between 70 and 90% of cases of AKI are community acquired. Most patients with AKI are young with a weighted mean age of 41.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 27 publications
0
28
1
Order By: Relevance
“…This prospective cohort study describes the profile of AKI in our daily practice. Numerous studies have shown that the epidemiology of AKI in developing countries is characterized by the young age of patients and a high incidence of infectious diseases 16 . However, data from sub-Saharan Africa published in recent years show that the average age of patients with AKI gradually increases, as is the case in our study 8,10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This prospective cohort study describes the profile of AKI in our daily practice. Numerous studies have shown that the epidemiology of AKI in developing countries is characterized by the young age of patients and a high incidence of infectious diseases 16 . However, data from sub-Saharan Africa published in recent years show that the average age of patients with AKI gradually increases, as is the case in our study 8,10 .…”
Section: Discussionmentioning
confidence: 99%
“…In African series, infections, toxins and gynaecologicalobstetrical causes are the main aetiologies of AKI 6,8,16 . The reduction of gynaecological-obstetrical AKI in our study is not only the result of public awareness of the risk of induced abortion, but also physicians training in Good Medical Practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute kidney injury (AKI) is a common medical problem among hospitalized patients and may be associated with multiple etiologies, occurring singly or in combination, including infectious diseases or conditions such as diarrheal disease, HIV, malaria, glomerulonephritis and sepsis, toxins or herbal medications, autoimmune diseases, pregnancy-related conditions, trauma-related tubular injury, and iatrogenic causes including medications such as nonsteroidal anti-inflammatory drugs, hypovolemia, and contrast induced nephropathy [ 1 , 2 ]. While there is limited data, the incidence of AKI among hospitalized patients in Africa is estimated at 0.3–1.9% [ 3 ]. Country specific studies such as those in Malawi found an incidence of AKI of 17.2% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute kidney injury is also reported in hospital admissions and may require renal replacement therapy in severe cases. Mortality rates of acute kidney injury in adults in Africa ranges from 13.5-43.5% [14] and may increase in settings where dialysis services are unavailable.…”
Section: Introductionmentioning
confidence: 99%